« How vaguely and slowly nations float about » : Patrick Leigh Fermor et le tempo du récit de voyage - Anne Duprat (Viatica)
Patrick Leigh Fermor crossed the twentieth century, from the interwar period to the beginning of the second millennium, from Crete to the Caribbean and from the Himalayas to the Andes, at the rhythm of walking, the only way to travel the world without ever ceasing to inhabit it. The article proposes an analysis of the evolution that leads his writing from distinguished adventure journalism to a literature of geographical imagination of profound originality. This process is accompanied by a work on the rhythm of the narrative, which sees Leigh Fermor’s writing advance, as it acquires literary depth, against not only the chronology of experience, but also, apparently, narrative efficiency. We show here that this expansion of a writing of the world, far from being detrimental to the dynamics of the narrative itself, gives birth on the contrary to a new ecological form of the travel narrative.